PERBAIKAN PENAMPILAN BUAH ABIU (Pouteria caimito Radlk.) MELALUI PEMBERONGSONGAN DAN APLIKASI PESTISIDA - Moh Nailun Ni'am; Slamet Susanto (Universitas Gunadarma, 2019)
Abiu is one of plant origin from Latin America, but it has been adapted and developed in Indonesia. Fruit defects are one of the main problem that decrease the performance quality of abiu. Fruit bagging combine with pesticides are expected to overcome tthe problem. This research aims to study the effect of many kinds of pesticide active compounds to abiu performance quality. This research was conducted at Desa Babakan Lebak, Kecamatan Kota Bogor Barat, and Post-harvest Laboratory of Agronomy and Horticulture, Bogor Agricultural University. The experimental design used was Random Complete Block Design one factor, with 10 replications. This research was consisted of five treatments as a single factor, those were bagging + profenofos 500EC (P1); bagging + Mankozeb 80WP and Streptomicyn sulfat 20WP (P2); bagging + propinep 70WP (P3), bagging without pesticides (P4), and control (P5). Result of this research indicated that treatment of bagging in combination with pesticide active compounds has significant effect on fruit appereance, especially in the fruit smoothnes. The best treatment is the combination of bagging with the addition of mankozeb and streptomycin sulfate pesticide active compounds, which can improve fruit smoothness 26% better than control. The treatment of pesticide active compounds didn’t have significan effectt on the diameter, softness, weight, volume, TSS, TTA, and vitamine C variables.